Examining the Issue of Undernutrition among Tribal Pregnant Women in Jammu Kashmir - Shafiya Rasheed, Dr. Keshlata (South Eastern European Journal of Public Health, 2025)
Undernutrition is a universal public health issue, particularly among pregnant women. Maternal malnutrition harms both mothers' and children's health, and as a result has significant impacts on economic and social development. One of the third goals established by the sustainable development Goals is to have good health and wellbeing.in order to achieve the goal maternal health becomes important. This paper investigates the significant issue of malnutrition among tribal pregnant women in Jammu and Kashmir. Cross sectional study was conducted among the tribal pregnant women, and it seeks to assess available literature, studies, and reports on the burden of undernutrition in this vulnerable population in depth. This research study uses a structured questionnaire, and the survey method was used to collect data.